Altered expression of genes related to innate antifungal immunity in the absence of galectin-3. Issue 1 (1st January 2021) - Rezende, Caroline Patini; Martins Oliveira Brito, Patricia Kellen; Pessoni, Andre Moreira; Da Silva, Thiago Aparecido; Goldman, Gustavo H; Almeida, Fausto
ABSTRACT: Galectin-3 (Gal-3) is the most studied member of the animal galectin family, which comprises β-galactoside-binding lectins and participates in several cellular events. Its expression in cells involved in innate and adaptive immunity is related to anti- and proinflammatory functions, signaling an important role in inflammatory, infectious, and tumorigenesis processes. Mice deficient in Gal-3 exhibit important phenotypes, but it is unclear whether these phenotypes reflect an impairment of the functions of this protein. Gal-3 plays an important role in modulating the immune response to different pathogenic microorganisms. However, the role of Gal-3 in immunity to infection is still poorly understood. Therefore, we investigated the effects of Gal-3 deletion on the expression of genes involved in the innate immune response in the lungs, spleens, and brains of Gal-3 KO mice. Gene profiling expression analysis suggested that Gal-3 deletion resulted in differentially modulated expression of the genes encoding beta-glucan, mannose and chitin-responsive pattern recognition receptors, signal transduction, inflammation, and phagocytosis. Our data thus suggest the importance of Gal-3 expression in the host innate immune system.